Bilateral impact of digital economy on air pollution: Emissions increase and reduction effects - Wang, Ruomei; Ding, Chenhui (Frontiers in Environmental Science, 2023)
China’s rapid industrialization and urbanization have led to ecological and environmental problems, particularly air pollution. Digitalization has become a key component in high-quality development to overcome the previous high-energy and high-pollution development model. However, a certain degree of “green blindness” exists in the digital development process, and the impact on air pollution is not always positive. Therefore, the impact of the digital economy on air pollution is worth exploring. In this study, we examines the emissions increase and reduction effect mechanisms of the digital economy on air pollution using panel data in 30 provinces in China from 2011 to 2020. The two-tier stochastic frontier model showed that the interaction between the emissions increase effect and emissions reduction effect of the digital economy reduced the actual air pollution emissions level below the frontier level by 0.15 %, on average. Overall air pollution level is characterized prominently by emission reduction, owing to the asymmetric bilateral effect of the digital economy. Second, the time trend characteristics of the net effect of the digital economy on air pollution emissions showed a wave-like change; the average values of the net effect in the three major regions (i.e., the east, central, and west) were all negative. Third, along with the development of digital economy, human capital levels, and general economic levels, the emissions reduction effect of the digital economy on air pollution has strengthened, such that the net effect became positive to negative. However, significant heterogeneous characteristics were noted in the effects of the digital economy on air pollution under different levels of digital economy development, human capital, and economic development. This study provides practical paths for air pollution management, strengthening inter-regional environmental synergy management and high-quality economic development.